Systematic review and meta‐analysis on the efficacy and tolerability of mirabegron for the treatment of storage lower urinary tract symptoms/overactive bladder: Comparison with placebo and tolterodine. (3rd December 2017) - Sebastianelli, Arcangelo; Russo, Giorgio I; Kaplan, Steven A; McVary, Kevin T; Moncada, Ignacio; Gravas, Stavros; Chapple, Christopher; Morgia, Giuseppe; Serni, Sergio; Gacci, Mauro
Abstract: A systematic review and meta‐analysis was carried out to evaluate the efficacy and safety of mirabegron 50 mg and 100 mg in the treatment of storage lower urinary tract symptoms/overactive bladder in comparison with a placebo and tolterodine 4 mg. A total of 491 articles were collected and eight randomized studies were identified as eligible for this meta‐analysis. Overall, eight trials were included in the meta‐analysis evaluating 10 248 patients. Mirabegron at both doses of 50 mg and 100 mg, and and tolterodine 4 mg were significantly associated with the reduction of incontinence episodes per 24 h, reduction of mean number of micturitions per 24 h, increase of voided volume and reduction of urgency episodes per 24 h, compared to a placebo. Both mirabegron 50 mg and mirabegron 100 mg were associated with a significant reduction of nocturia episodes when compared with a placebo. Conversely, tolterodine 4 mg did not prove to be more effective than a placebo in the reduction of nocturia episodes. Furthermore, mirabegron 50 mg showed a slightly, but significantly, better efficacy than tolterodine 4 mg in the improvement of nocturia episodes. Mirabegron 50 mg and mirabegron 100 mg shared the same risk of overall treatment‐emergent adverse events rate with the placebo. Otherwise, tolterodine 4 mg was associated with a significantly greater risk than the placebo. However, mirabegron 100 mg showed a slight trend toward an increased risk of hypertension (odds ratio 1.41; P = 0.08) and cardiac arrhythmia (odds ratio 2.18; P = 0.06). Mirabegron is an effective treatment for patients with storage lower urinary tract symptoms/overactive bladder, providing a reduction of incontinence, urgency and frequency; an improvement of voided volume with a slight, but statistically, significant improvement of nocturia; with a good safety profile. These findings should be considered for the treatment planning of patients with storage lower urinary tract symptoms/overactive bladder.